1995
DOI: 10.1300/j010v21n04_02
|View full text |Cite
|
Sign up to set email alerts
|

Educating African-Americans About Cancer Prevention and Detection:

Abstract: The high incidence of cancer mortality and morbidity among African-Americans has led to a need for cancer education and detection programs designed for this underserved population. This review of the literature focuses on key cancer-related health beliefs, barriers to utilization, and methods of intervention that should be considered in developing programs for African-Americans. Implications for social work practice are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The majority of respondents felt that health education was a top priority in their community [11]. Also, many African Americans have a false perception that the incidence of cancer is lower in African Americans than in Caucasians [12]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of respondents felt that health education was a top priority in their community [11]. Also, many African Americans have a false perception that the incidence of cancer is lower in African Americans than in Caucasians [12]. …”
Section: Discussionmentioning
confidence: 99%
“…Salber et al [15] have identified additional functions of the lay health advisor that include strengthening professionals' ties with the community, channeling knowledge to and from the community, bidirectional education of community members on the role and function of the health care system and of professionals about the lay advising system, informing the community about available resources, improving the helper's role in helping others and helping the community to better cope with health care problems. Lay health advisors also mobilize community resources to sustain and support the health care system [16]. …”
Section: Discussionmentioning
confidence: 99%
“…These factors may have some influence on stage at detection in particular. They include various beliefs about cancer risk and the usefulness of early detection, differences in the effects of various outreach and reminder strategies, differences in access mediated by transportation or the ability to get time off from work to keep appointments, obesity, comorbidities, and nrnnnTO differences in breast density that modify the effectiveness of mammograms (4,11,23,(29)(30)(31)(32)(33). A fundamental question for us, and for the related studies we cite, is whether African-American women have intrinsically more aggressive tumors than EuropeanAmerican women, thus affecting their survival either directly or by way of stage at detection because of more rapid progression.…”
Section: Discussionmentioning
confidence: 99%
“…These factors may have some influence on stage at detection in particular. They include various beliefs about cancer risk and the usefulness of early detection, differences in the effects of various outreach and reminder strategies, differences in access mediated by transportation or the ability to get time off from work lo keep appointments, obesity, comorbidities, and differences in breast density that modify the effectiveness of mammograms (4,11,23,(29)(30)(31)(32)(33). A fundamental question for us, and for the related studies we cite, is whether African-American women have intrinsically more aggressive tumors than EuropeanAmerican women, thus affecting their survival either directly or by way of stage at detection because of more rapid progression.…”
Section: Discussionmentioning
confidence: 99%